LEGAL ASPECTS OF THE STUDY OF THE WORK “THE LAWS OF TIMUR” (World Bulletin of Management and Law, 2022)
The article reflects on the legal basis of the work of Timur's structures. It presents the source characteristics of legal concepts in the management of the important foundations of statehood. In the statehood of Amir Timur, the criterion of the idea of building a fair society is determined